A LINGUO-CULTURAL APPROACH TO METAPHOR CLASSIFICATION: UNVEILING CULTURAL CONCEPTS THROUGH FIGURATIVE LANGUAGE (Scientific journal of the Fergana State University, 2024)
This article analyzes in detail the classification of linguistic and cultural metaphors in literary texts. Using a linguocultural approach, we analyzed metaphors from such works as “Pride and Prejudice” by Jane Austen, Charlotte Bronte’s “Jane Eyre” and “The House of Mirth” Edith Wharton, and explored the cultural concepts that are ingrained in them. By studying both common and unique metaphorical expressions, we have given our own judgment on how metaphors reflect and shape cultural identity. The methods of semantic-stylistic, linguistic-cultural, descriptive, and comparative analysis were used in the research process. The results of our study revealed important linguistic and cultural features and showed the effectiveness of the linguistic and cultural approach to metaphorical analysis.